Application of Moral Value Planting Methods by Teachers to Students at Qatrinnada Islamic PAUD Kelurahan Pasia Nan Tigo Kecamatan Koto Tangah Kota Padang - Fitri Andrian (Universitas Negeri Padang, 2019)
Background of this study by by the planting of moral values in Qatrinnada Islamic PAUD running well even though the education level of the coastal communities is low and parents of children with eyes for the search for fishermen and freelancers, so that parents cannot provide examples of planting good and appropriate behavior for their children in Qatrinnada Islamic PAUD. The purpose of this study is to describe the planting of moral values by teachers through the method of play, the cultivation of moral values through the method of giving assignments, and the cultivation of moral values through the method of conversation. This study is a quantitative descriptive study, with a population of 70 children, a sample of 45% of the population, 30 people with a proportional random sampling technique. Data collection techniques using questionnaires, and data collection tools using questionnaires. The analysis techniques use the percentage formula. The results of the study show that (1) the method of playing on the cultivation of moral values in good categories, (2) the method of giving assignments used by the teacher to planting moral values in good categories, and (3) the method of conversations used in planting moral values in good categories. It is recommended to the school and parents at home to improve the game method, the method of conversing on planting moral values.Keywords: Value, Morale, PAUD